Traumatic aneurysms and arterial venous fistulas - Cuacci, Oscar; Grinfeld, David; Lanari, Néstor (Cirugía del Uruguay, 1978)
The authors analize the clinic and the complications of the traumatic aneurysms arterial-venous fistulas. They state the general proceedings f<ir its surgical treatment.